2000
DOI: 10.1111/j.1151-2916.2000.tb01688.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Tensile Deformation of Glass‐Doped 3Y‐TZP

Abstract: Amorphous grain boundary phases in 3-mol%-yttriastabilized zirconia ceramics (3Y-TZP) were studied to determine the influence of intergranular amorphous silicate phases on tensile superplasticity at temperatures of 1300 -1500°C. Controlled additions (1 wt%) of compositionally distinct barium silicate and borosilicate phases were used. The initial grain sizes of the pure, barium silicate added, and borosilicate-added samples were 0.45, 0.55, and 0.55 m, respectively. Systems with added barium silicate and boros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Imamura et al also reported that covalency would affect on tensile ductility in glass-doped TZP. 15) Our calculation reveals that substitution of Ge 4+ or Ti 4+ ions reinforces covalent bonding strength in a bulk of TZP. In cation-doped TZP, the segregation of dopant cations at grain boundary is observed through TEM-EDS analysis.…”
Section: Chemical Bonding Sates In Geo 2 or Tio 2 -Doped Tzpmentioning
confidence: 72%
“…Imamura et al also reported that covalency would affect on tensile ductility in glass-doped TZP. 15) Our calculation reveals that substitution of Ge 4+ or Ti 4+ ions reinforces covalent bonding strength in a bulk of TZP. In cation-doped TZP, the segregation of dopant cations at grain boundary is observed through TEM-EDS analysis.…”
Section: Chemical Bonding Sates In Geo 2 or Tio 2 -Doped Tzpmentioning
confidence: 72%
“…The lower temperature plasticity of ceramics combined with high strength might improve their in-service reliability through metal-like behavior. Two strategies are generally chosen to improve plasticity at relatively low temperatures [7][8][9][10]: (1) decreasing grain size to several nanometers to promote grain boundary sliding; (2) accelerating grain boundary diffusion with low melting point sintering additives. However, it is di cult to sinter dense nanoceramics with grains of less than 10 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocrystalline silicon carbide doped with boron and carbon was found to show a superplastic elongation of > 140% at 1800°C with a yield stress of 80 MPa [8]. In Imamura et al's studies about high-temperature deformation of 3Y-TZP, an addition of only 1 wt% amorphous silicate was found to decrease the ow stress by 50% at 1500°C [9].…”
Section: Introductionmentioning
confidence: 99%
“…5) The effects of additional glass on superplasticity of YTZP have been studied to improve the ductility 6) 11) Yoshizawa et al 6) and Gust et al 7) reported that the addition al silicate glass was present not only at multiple junctions as glass pocket but also at twograin junctions as thin film. However, Ikuhara et al 9) revealed that intergranular glass film did not exist in SiO 2 doped YTZP.…”
Section: Introductionmentioning
confidence: 99%